Associations among histological characteristics and patient outcomes in colorectal carcinoma with a mucinous component. Issue 3 (11th November 2018) - Gonzalez, Raul S; Cates, Justin M M; Washington, Kay
Abstract : Aims: Colorectal carcinoma (CRC) often has a mucinous component, with more than 50% mucin by volume defining the mucinous subtype of CRC. The prognostic impact of the mucinous phenotype remains unclear. Methods and results: We evaluated 224 CRC with at least 5% mucinous component (herein 'mCRC') for patient sex, age, race and outcome; tumour size, location, stage and microsatellite instability (MSI) status; percentage of glands producing mucin; percentage of tumour volume composed of mucin; whether tumoral epithelium floated in mucin pools; tumour budding; signet ring cells (SRCs); and peritumoural inflammation (PI). We related these features to disease‐specific survival and compared outcomes to 499 stage‐matched, conventional colorectal adenocarcinomas. Factors predicting worse prognosis in mCRC on univariable analysis included non‐MSI‐high status ( P  = 0.0008), SRC ( P  = 0.0017) and lack of PI ( P  = 0.0034). No parameters were independently associated with outcome after adjusting for tumour stage in multivariate analysis. The percentage of glands producing mucin and percentage tumour volume composed of mucin did not affect prognosis, including at the recommended 50% cut‐off for subtyping mCRC. Disease‐specific survival for mCRC and adenocarcinomas were similar after accounting for stage. Conclusions: Stage‐matched mCRCs and adenocarcinomas have similar outcomes, with no prognostic significance to morphological subtyping. Histological characteristics of mCRC, including percentage of tumour volume comprised of mucin, were not predictive of outcome.